2020
DOI: 10.1051/0004-6361/201937030
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Gravitationally lensed Objects in HSC Imaging (SuGOHI)

Abstract: Strong gravitationally lensed quasars provide powerful means to study galaxy evolution and cosmology. We use Chitah to hunt for new lens systems in the Hyper Suprime-Cam Subaru Strategic Program (HSC SSP) S16A. We present 46 lens candidates, of which 3 are previously known. Including 2 additional lenses found by YattaLens, we obtain X-shooter spectra of 6 promising candidates for lens confirmation and redshift measurements. We report new spectroscopic redshift measurements for both the lens and source galaxies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 79 publications
0
55
0
Order By: Relevance
“…We compiled grade A and B systems (or equivalent) from a number of recent searches based on optical and near-infrared imaging from DES (Diehl et al 2017;Jacobs et al 2019b,a), CFHTLS (More et al 2016;Jacobs et al 2017), KiDS (Petrillo et al 2017(Petrillo et al , 2019Li et al 2020), DESI (Huang et al 2020a), and HSC (Wong et al 2018;Sonnenfeld et al 2018Sonnenfeld et al , 2020Jaelani et al 2020). Since our network may also be sensitive to lensed quasars with colors and configurations similar to our mock lenses, we also cross-matched with the all-sky database of ∼220 confirmed lensed quasars in the literature (Lemon et al 2019, and references therein) 12 , and with previously identified lensed quasars from HSC (Chan et al 2020) and from PS1 (Rusu et al 2019). For the candidates not included in those tables, we searched in the SIMBAD Astronomical Database 13 .…”
Section: Final Candidates From Visual Inspectionmentioning
confidence: 99%
“…We compiled grade A and B systems (or equivalent) from a number of recent searches based on optical and near-infrared imaging from DES (Diehl et al 2017;Jacobs et al 2019b,a), CFHTLS (More et al 2016;Jacobs et al 2017), KiDS (Petrillo et al 2017(Petrillo et al , 2019Li et al 2020), DESI (Huang et al 2020a), and HSC (Wong et al 2018;Sonnenfeld et al 2018Sonnenfeld et al , 2020Jaelani et al 2020). Since our network may also be sensitive to lensed quasars with colors and configurations similar to our mock lenses, we also cross-matched with the all-sky database of ∼220 confirmed lensed quasars in the literature (Lemon et al 2019, and references therein) 12 , and with previously identified lensed quasars from HSC (Chan et al 2020) and from PS1 (Rusu et al 2019). For the candidates not included in those tables, we searched in the SIMBAD Astronomical Database 13 .…”
Section: Final Candidates From Visual Inspectionmentioning
confidence: 99%
“…Since these strong lens observations are very powerful, several large surveys including the Sloan Lens ACS (SLACS) survey (Bolton et al 2006;Shu et al 2017), the CFHTLS Strong Lensing Legacy Survey (SL2S; Cabanac et al 2007;Sonnenfeld et al 2015), the Sloan WFC Edge-on Late-type Lens Survey (SWELLS; Treu et al 2011), the BOSS Emission-Line Lens Survey (BELLS; Brownstein et al 2012;Shu et al 2016;Cornachione et al 2018), the Dark Energy Survey (DES; Dark Energy Survey Collaboration 2005; Tanoglidis et al 2021), the Survey of Gravitationally-lensed Objects in HSC Imaging (SuGOHI; Sonnenfeld et al 2018a;Wong et al 2018;Chan et al 2020;Jaelani et al 2020), and surveys in the Panoramic Survey Telescope and Rapid Response System (Pan-STARRS; e.g., Lemon et al 2018;Cañameras et al 2020) have been conducted to find lenses. So far we have detected several thousand lenses, but mainly from the lower redshift regime.…”
Section: Introductionmentioning
confidence: 99%
“…The steps described above led us to a sample of ∼300 000 galaxies. From these, we removed 70 known lenses from the literature, mostly from our previous searches (Sonnenfeld et al 2018;Wong et al 2018;Chan et al 2020), as well as a few hundred galaxies that have already been inspected and identified as possible lenses (grade C candidates in our notation) in the aforementioned studies. Many of the known lenses were used for training purposes, which is further explained in Sect.…”
Section: The Parent Samplementioning
confidence: 99%
“…The blue portion of the histogram corresponds to lenses discovered in this study. The green part indicates BOSS galaxy lenses discovered with YattaLens, presented in Paper I, II, and IV (Sonnenfeld et al 2018;Wong et al 2019;Chan et al 2020). The cyan part shows lenses discovered by means of visual inspection of galaxy clusters, as presented in Paper V. The striped regions indicate lenses discovered independently in this study and in the study of Paper V. Grey solid lines: distribution in lens spectroscopic redshift of lenses from the Sloan ACS Lens Survey (SLACS, Auger et al 2010).…”
Section: A Diverse Population Of Lensesmentioning
confidence: 99%